Improving the efficiency of technological gas low-temperature separation unit devices using simulation dynamic model; Chemical Reactors (CHEMREACTOR-22) - Pisarev M. O. Mikhail Olegovich; Dolganov I. M. Igor Mikhailovich; Dolganova I. O. Irena Olegovna; Ivashkina E. N. Elena Nikolaevna (2016, 2016)
Title screen